Gaps in the legislation halal in Malaysia: a study of literature - Soraji, Azis Jakfar; Awang, Mohd Daud; Mohd Yusof, Ahmad Nasir (International Organization Center of Academic Research, 2017)
Islam is a well known religion that is perfect, complete, and the rules covering all aspects of human life to achieve happiness in this world until hereafter. Islam encouraging on its followers to choose the good path in every aspect of life, including social, economic and political. In Malaysia, several regulations have been put in place relating to certification or halal labeling. The main complaints related to the halal certification in Malaysia regarding the existence of a number of halal certification bodies, which have created confusion among users of Islam and law enforcement issues halal. The purpose of this article is to analyze the reasons for these discrepancies and offer some practical solutions from a legal standpoint. The research methodology that had been used in this paper is library research methods. The descriptive analysis and content of reading material and relevant law provisions used in the discussion. The findings from the analysis of the data collected shows that the provisions of existing laws, especially the Trade Descriptions Act 2011, are not equipped to deal with the issues and challenges for halal certification while, especially regarding the control over the bodies of halal certification which offers halal certification people and issues of enforcement and prosecution. In addition, the absence of a lawful act is also a challenge to those responsible for working towards the formulation and eventually to be implemented, especially in Malaysia.